Penerapan Metode Case Based Reasoning Pada Sistem Pakar Untuk Mendiagnosa Gangguan Tanaman Jeruk Semboro - Yanuar Nurdiansyah; Riska Arimanudin (Faculty of Computer Science, University of Jember, 2017)
Orange is a flowering plant surnamed Citrus from Rutaceae tribe. Oranges are one of the most important fruit plants that are given top priority to be developed nationally. Jember regency is the centre of producer of Jeruk Siam in East Java which is often known as Jeruk Semboro. A lot of types of pests or diseases in oranges plants result in the need of an agricultural consultant who is able to diagnose pests or diseases that contribute oranges crops. However, time and cost are the reasons for oranges farmers not to consult experts so there is often a mistake in providing solutions to the plants that have been attacked. To overcome this problem, then built expert system to diagnose the disturbance of citrus plants by applying the method of case-based reasoning where this system can diagnose pest or disease of oranges plant by imitating expert way of work. Case Based Reasoning (CBR) is one method that uses artificial intelligence approach (artificial intelligent) which emphasizes problem solving on knowledge from previous cases. It is hoped that by applying the case based reasoning method to the expert system to diagnose the disturbance of citrus in citrus citrus plant is able to help the citrus farmers to diagnose the disturbance of orange either disturbance from pest or disease. This system has been through two testing methods, the first test using a comparison of manual calculations with the system, the second test using recapitulias evaluation results to test the accuracy of the diagnosis. Test results using both methods found that the Expert System to Diagnose Semboro Citrus Disorder has a validity and decision-making with a percentage of 80%.